Bioaccumulation of poly-aromatic hydrocarbons in plankton, algae and fish in south sea waters in Jogjakarta - Endang Lukitaningsih; Ari Sudarmanto (Indonesian Journal of Pharmacy, 2010)
As  a  pollutant,  the  presence  of Poly  Aromatic  Hydrocarbons  (PAH)  in  the environment must be always monitored, because of their ability to spread widely through  the  food  chain  and  also  their  carsinogenic  properties.  The  solubility  of PAH  in  water  is  very  low,  therefore  it  is  difficult  to  analyze  their  presence  in water environment by using water as a sample. By utilizing the phenomenon of the  accumulation  of  PAH  in  biolipids,  the  analysis  method  has  been  developedusing  bioindicators.  In  this  research,  the  concentration  of  four  kinds  of  PAH (pyrene,  benzo(a)anthracene,  benzo(k)fluoranthene  and  perylene)  in  several samples  (water,  plankton,  algae  and  fish)  that  collected  from  the  south  sea Jogjakarta  has  been  determined. The bioaccumulation  factor  (BAF)  of  PAH  in each  sample  has  been  calculated  and  the  results  were  from  4498  to  432754; 2552  to  49265;  14156  to  730991,  respectively  for  plankton,  algae  and  fish. Based on the BAF values, plankton can be used as a bioindicator for short term PAH monitoring, while the Upeneus moluccensisfish primarily gills organ can be used as a bioindicator for medium term (months) PAH monitoring.Key  words  :  poly  aromatic  hydrocarbons,  bioaccumulation  factor,  bioindicator,  Upeneus moluccensis